Mckusick-Kaufman Syndrome Presenting as Acute Intestinal Obstruction - Ramesh B Hatti; Ashok V Badakali; R N Vanaki; VijayMahantesh S Samalad (EL-Med-Pub, 2013)
Hydrometrocolpos and polydactyly have been associated with many syndromes and can present at any age. Rarely does hydrometrocolpos present as neonatal intestinal obstruction. We report two cases of McKusick-Kaufman syndrome presenting with intestinal obstruction. In both cases, intestinal obstruction got relieved after a cutaneous vaginostomy.